Flutiform, a new steroid/long‐acting beta‐agonist inhaler. Issue 8 (22nd April 2013) - Chaplin, Steve; Thomson, Neil
Abstract Flutiform is a new inhaled steroid/long‐acting beta‐agonist combination containing fluticasone and formoterol. Here, the authors give details of the clinical trial results regarding its efficacy and safety and discuss its place in the treatment of asthma.